Ritmos temporales y dinámicas del paisaje de la alta Alpujarra Granadina mediante Sistemas de Información Geográfica - Camacho Olmedo, María Teresa (Geographicalia, 2016)
In the lasts decades the mediterraneans mountains landscapes have been reorganized. In the region named Alta Alpujarra, the landscape has been afected by the agricultural’s abandon and the vegetation commuunities progression in theses places. In the other hand, the pine’s reforestation has changed the middle mountain and the oaks arid ilex’s commmunities advances in a natural process. A cronological serie of land use maps in the second half of XX century has been builded wihi a Geographical Information System, where the legend includes the more cornplex situations specially those from the transitions between categories and from the mosaic landscape. This serie is the first step for the spatial and temporal analysis, made by the fonctions of the GIS, to show the principals dynamics, the temporal rhythms and the globals changes diagnostics.